2020
DOI: 10.4102/sajip.v46i0.1754
|View full text |Cite
|
Sign up to set email alerts
|

The validation of the servant leadership scale

Abstract: Research approach/design and method: A convenience sample of 1764 respondents, employed in both private and public sectors (employed in 31 different organisations), relatively well representative of the South African workforce in general, was used for this study.Main findings: An exploratory and confirmatory factor analysis yielded a one-factor solution of servant leadership that has acceptable psychometric and fit properties. The instrument was further found to have adequate convergent validity (compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…The SLQ7 uses a 7-point Likert scale, ranging from strongly disagree (1) to strongly agree (7). Liden et al (2015) reported acceptable reliabilities of 0.80, 0.81 and 0.89 across three independent samples for the SLQ7, while Grobler and Flotman (2020)…”
Section: Servant Leadershipmentioning
confidence: 94%
See 2 more Smart Citations
“…The SLQ7 uses a 7-point Likert scale, ranging from strongly disagree (1) to strongly agree (7). Liden et al (2015) reported acceptable reliabilities of 0.80, 0.81 and 0.89 across three independent samples for the SLQ7, while Grobler and Flotman (2020)…”
Section: Servant Leadershipmentioning
confidence: 94%
“…The 7-item SL questionnaire (SLQ7), developed by Liden et al (2008), was used to measure SL. To determine the structural validity of the instrument for the South African population, Grobler and Flotman (2020) confirmed the unidimensional nature of the original SLQ7. A typical item of the SLQ7 reads 'My leader can tell if something work-related is going wrong' (item 1).…”
Section: Servant Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers, such as Bolden and Kirk (2005), Chasi and Levy (2016), Chatbury, Beaty andKriek (2011), Littrell andNkomo (2005), Spangenberg and Theron (2016) and Walumbwa et al (2011), make compelling arguments that Africa has its own values and practices, and that these should be an integral part of leadership practices for the continent. The authors, such as Obiakor (2004), Grobler and Singh (2018), Grobler and Flotman (2020) and Msila (2008), have criticised Western theories on practices of leadership in the African context outright and have called for an African-centred leadership approach that is relevant to the values of Africans. Whilst these researchers (Grobler & Flotman, 2020;Grobler & Singh, 2018;Msila, 2008;Obiakor, 2004) argue against the Eurocentric approach to leadership and leadership development programmes, they provide no evidence of a clear definition of what leadership is for Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The authors, such as Obiakor (2004), Grobler and Singh (2018), Grobler and Flotman (2020) and Msila (2008), have criticised Western theories on practices of leadership in the African context outright and have called for an African-centred leadership approach that is relevant to the values of Africans. Whilst these researchers (Grobler & Flotman, 2020;Grobler & Singh, 2018;Msila, 2008;Obiakor, 2004) argue against the Eurocentric approach to leadership and leadership development programmes, they provide no evidence of a clear definition of what leadership is for Africa.…”
Section: Introductionmentioning
confidence: 99%